A Roadmap to Cardiac Tissue‐Engineered Construct Preservation: Insights from Cells, Tissues, and Organs. Issue 27 (28th May 2021) - Sampaio‐Pinto, Vasco; Janssen, Jasmijn; Chirico, Nino; Serra, Margarida; Alves, Paula M.; Doevendans, Pieter A.; Voets, Ilja K.; Sluijter, Joost P. G.; van Laake, Linda W.; van Mil, Alain
Abstract: Worldwide, over 26 million patients suffer from heart failure (HF). One strategy aspiring to prevent or even to reverse HF is based on the transplantation of cardiac tissue‐engineered (cTE) constructs. These patient‐specific constructs aim to closely resemble the native myocardium and, upon implantation on the diseased tissue, support and restore cardiac function, thereby preventing the development of HF. However, cTE constructs off‐the‐shelf availability in the clinical arena critically depends on the development of efficient preservation methodologies. Short‐ and long‐term preservation of cTE constructs would enable transportation and direct availability. Herein, currently available methods, from normothermic‐ to hypothermic‐ to cryopreservation, for the preservation of cardiomyocytes, whole‐heart, and regenerative materials are reviewed. A theoretical foundation and recommendations for future research on developing cTE construct specific preservation methods are provided. Current research suggests that vitrification can be a promising procedure to ensure long‐term cryopreservation of cTE constructs, despite the need of high doses of cytotoxic cryoprotective agents. Instead, short‐term cTE construct preservation can be achieved at normothermic or hypothermic temperatures by administration of protective additives. With further tuning of these promising methods, it is anticipated that cTE construct therapy can be brought one step closer to the patient. Abstract : Successful preservation methods for cardiac‐tissue‐engineered constructs will allow transportation and storage for off‐the‐shelf availability, both critical for translating this technology to clinical use, opening new avenues for the treatment/prevention of heart failure. A theoretical foundation for cardiac‐tissue‐engineered construct preservation is presented, with the aim to provide a roadmap to design safe and robust storage protocols.